Internet of Things: A Hypothetical and Prototyping Platform for CRASP Methodology - Tatapudi, Gopikrishna (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
The construction industry has always been considered one of the most dangerous industrial sectors. Construction workers are often exposed to considerable risks, including falling from heights, unguarded machinery, or being stuck by heavy construction equipment. The construction business employs both skilled and unskilled laborers susceptible to accidents and health hazards on the construction site. Numerous accidents occur at construction sites despite the existence of labor safety rules. A Korean case study statistics showed the significance of construction health and safety management. By adopting CRASP methodology and applying innovative methods such as the intervention of ICT and the IoT, i.e., the prototype development through the Arduino platform could implement the automated features of construction health and safety management features. This research concludes that the CRASP conceptual methodology could be adaptable that drives the manifestation of IoT-based prototyping. IoT-based prototype functional features showed the feasibility of implementing automated construction health and safety management on-site.